2021
DOI: 10.22146/jieb.59893
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Incentives and Leadership Styles on Creative Performance

Abstract: Introduction/Main Objectives: This study investigates whether the type of incentives offered and leadership styles interact to affect creative performance. Background Problems: Creativity is highly needed by companies to survive in a volatile business environment. Prior research found that management control systems and the leadership style were able to stimulate creativity. It is still unclear which type of incentives and leadership styles are able to stimulate creativity. Therefore, this research proposes a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…The good leader must demonstrate communication skills, interpersonal interaction, the ability to obtain useful and ongoing information on the progress of projects, openness and appreciation of subordinates' ideas and empathy for their moods, and the ability to use interpersonal networks to provide and receive project-relevant information. If this behaviour is permanent, it can produce significant improvements in employee thoughts, attitudes, and creative performance (Ilyana & Sholihin, 2021). On a broader level, leaders who wish to support high-level performance need to pay special attention to the details of their daily attitude towards their work team.…”
Section: Discussionmentioning
confidence: 99%
“…The good leader must demonstrate communication skills, interpersonal interaction, the ability to obtain useful and ongoing information on the progress of projects, openness and appreciation of subordinates' ideas and empathy for their moods, and the ability to use interpersonal networks to provide and receive project-relevant information. If this behaviour is permanent, it can produce significant improvements in employee thoughts, attitudes, and creative performance (Ilyana & Sholihin, 2021). On a broader level, leaders who wish to support high-level performance need to pay special attention to the details of their daily attitude towards their work team.…”
Section: Discussionmentioning
confidence: 99%
“…Berraies & Zine El Abidine (2019) also conclude that the leadership style promotes ambidextrous innovation. For improving the creative performance, employees need to be empowered because they need the authority and freedom to develop their ideas (Ilyana and Sholihin, 2021).…”
Section: Relationship Between Leadership and Innovative Work Behaviormentioning
confidence: 99%
“…[16] proved that ineffective incentive systems affect turnover intention by reducing organizational commitment. Furthermore, research [17] found that the interaction between incentives and leadership style in influencing creative performance is not significant. [18] found that incentives could not effectively moderate the relationship between working hours and turnover intention among doctors.…”
Section: Introductionmentioning
confidence: 99%